Construction and Validation of a Universal Applicable Prognostic Signature for Gastric Cancer Based on Seven Immune-Related Gene Correlated With Tumor Associated Macrophages - Huo, Junyu; Wu, Liqun; Zang, Yunjin (Frontiers in Oncology, 2021)
Background: Tumor associated macrophages (TAMs) played an critical role in the progression of malignant tumors, but the detailed mechanism of TAMs in gastric cancer(GC) is still not fully explored. Methods: We identified differential expressed immune-related genes(DEIRGs) between the high- and low macrophage infiltration GC samples in The Cancer Genome Atlas datasets. A risk score was constructed basing on univariate Cox analysis and Lasso penalized Cox regression analysis in the TCGA cohort(n=341). The optimal cutoff determined by the 5-year time depend receiver operating characteristic(ROC) curve was considered to classify patients into groups with high and low risk. We conducted external validation of the prognostic signature in four independent cohorts(GSE84437,n=431; GSE62254, n=300; GSE15459, n=191; GSE26901, n=109) from the Gene Expression Omnibus (GEO) database. Results: The signature consisted of 7 genes(FGF1, GRP, AVPR1A, APOD, PDGFRL, CXCR4, and CSF1R) showed good performance in predicting the overall survival(OS), in the 5 independent cohorts. The risk score presented obviously positive correlation with the macrophage abundance(cor=0.7, p<0.001). A significant difference was found between the high- and low-risk group in the in the overall survival of GC patients. The high-risk group exhibited higher infiltration level of Macrophages M2 estimated by the CIBERSORT algorithm. In the five independent cohort, the risk score was highly positively correlated with the stromal cell score, suggesting that we can also evaluate the infiltration of stromal cells in tumor microenvironment according to the risk score. Conclusion: Our study developed and validated an general applicable prognostic model for GC from the perspective of TAMs, which may help to improve the precise treatment strategy of GC.